2018
DOI: 10.1111/1440-1681.13026
|View full text |Cite
|
Sign up to set email alerts
|

Pectic polysaccharides extracted from Rauvolfia verticillata (Lour.) Baill. var. hainanensis Tsiang ameliorate ulcerative colitis via regulating the MAPKs and NF‐κB pathways in dendritic cells

Abstract: This study was to investigate the effects and mechanisms of pectic polysaccharides (PP) extracted from Rauvolfia verticillata (Lour.) Baill. var. hainanensis Tsiang on dextran sulphate sodium (DSS)-induced ulcerative colitis (UC). Eighty female BALB/c mice were randomly divided into four groups: Control, DSS, DSS + salicylazosulfapyridine (SASP), and DSS+ PP. The disease activity index (DAI), overall physical activity, and blood stool were monitored daily to evaluate severity of UC. Histological scores of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Its roots and leaves are used for medicinal purposes including treating hypertension, hyperthermia, insomnia, and so on (Hong et al, 2012). Miao et al (2019) obtained a pectic polysaccharide PP from the rootstocks of R. verticillata and found that PP treatment attenuated the overall physical activity, DAI, and morphological damage in DSS-treated colitis mice. Meanwhile, PP dramatically reduced TNF-α, IL-6, and MPO activity.…”
Section: Rauvolfia Verticillatamentioning
confidence: 99%
“…Its roots and leaves are used for medicinal purposes including treating hypertension, hyperthermia, insomnia, and so on (Hong et al, 2012). Miao et al (2019) obtained a pectic polysaccharide PP from the rootstocks of R. verticillata and found that PP treatment attenuated the overall physical activity, DAI, and morphological damage in DSS-treated colitis mice. Meanwhile, PP dramatically reduced TNF-α, IL-6, and MPO activity.…”
Section: Rauvolfia Verticillatamentioning
confidence: 99%
“…It has been well established that TLR4-mediated activation of NF-κB, a vital transcript factor involved in inflammation, is crucial in regulating intestinal inflammation. [27][28][29] Activation of the NF-κB signaling pathway in macrophages is associated with increased production of proinflammatory cytokines. 30 We have previously found that TLR4 is one of the important regulators of the NF-κB pathway in macrophages.…”
Section: Conflict Of Interestsmentioning
confidence: 99%
“…Since they are food polysaccharides, they are a less toxic and effective therapeutic option (20). Studies have shown that PPs from Rauvolfia verticillata have therapeutic effects against UC (7)(8)(9)(10). Intestinal mucosal immunity plays an important role in the pathogenesis of intestinal inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…However, their mechanisms of action have not been established. Previous studies have shown that Rauvolu hainanensis extracts, especially PPs, inhibited the progression of dextran sulfate sodium (DSS)-induced colitis in mice by regulating the nuclear factor (NF)-κB pathway and interleukin (IL)-17 (9,10). Other reports have demonstrated that its mechanisms may be associated with the NF-κB and mitogen-activated protein kinase (MAPK) signaling pathways in which dendrites derived from mouse bone marrow shape cells play an essential role (10).…”
Section: Original Articlementioning
confidence: 99%
See 1 more Smart Citation